ENHANCING DIGITAL COMPETENCE AND ENGLISH LANGUAGE PROFICIENCY THROUGH MOBILE APPLICATIONS: A MULTI APPLICATION PEDAGOGICAL MODEL - Yuldashev Sherzod Zairjanovich; Taryanikova Marina Anatolievna (Bright Mind Publishing, 2025)
This study examines a multi-application model for integrating mobile applications into English language instruction to enhance both language proficiency and digital competence among university students. Conducted at ISFT Institute with 40 second-year students, the research employed an experimental-control group design. The experimental group used Kahoot, Gimkit, Quizlet, Memrise, Duolingo, Busuu, BBC Learning English, EWA English, HelloTalk, and Tandem, while the control group followed traditional textbook-centered instruction. Data was collected through pre- and post-tests, motivation surveys, and observed participation patterns. Results show that the multi-application model improved vocabulary acquisition, listening comprehension, digital literacy, communication confidence, and motivation. The findings support the inclusion of diverse digital tools in language pedagogy to create interactive, student-centered learning environments and promote autonomous learning.